Investment in the Euro Area : Why Has It Been Weak? - Barkbu, Bergljot (IMF Working Papers; Working Paper ;, 2015)
Investment across the euro area remains below its pre-crisis level. Its performance has been weaker than in most previous recessions and financial crises. This paper shows that a part of this weakness can be explained by output dynamics, particularly before the European sovereign debt crisis. The rest is explained by a high cost of capital, financial constraints, corporate leverage, and uncertainty. There is a considerable cross country heterogeneity in terms of both investment dymanics and its determinants. Based on the findings of this paper, investment is expected to pick up as the recovery strengthens and uncertainty declines, but persistent financial fragmentation and high corporate leverage in some countries will likely continue to weigh on investment.